Inference and applications of genetic relatedness in human populations - Nait Saada, J (2022)
Exploring the human genome holds benefits for many fields, which include molecular medicine, human evolution, population genetics and genetic epidemiology. The human genome contains around 3 billion base pairs and approximately 99.9 percent of these base pairs are identical between any two individuals. Differences in the remaining 0.1 percent could explain the astonishing variety between individuals - not only in appearance, but also in health.